REPRESENTASI IDENTITAS DAN GASTRONOMI BUDAYA KULINER JAWA DALAM LIMA LAGU KARYA KI NARTO SABDO - Pratama, Aditya; -, Darmoko; Prasetiyo, Ari; Retno Mastuti, Dwi Woro (Paradigma: Jurnal Kajian Budaya, 2026)
Culinary is not just food and drink, but has transformed into a study of culinary gastronomy which focuses on aspects of history, values, philosophy, taste and components. The study of the problems discussed in this research is related to the cultural identity of Javanese culinary gastronomy in the five songs by Ki Narto Sabdo. Descriptive qualitative research methods with an objective approach were applied in this research. This research uses Santich's culinary gastronomy theory and Stuart Hall's theory of cultural identity representation with a constructionist approach. As a result, the representation of Javanese culinary gastronomic cultural identity is built on culinary gastronomic components such as ingredients, method of preparation, shape, taste, color, values and benefits. These five do not contain all the components in one song, but only some components. The gastronomic component in each song becomes its own characteristic of the culinary delights. Apart from that, the representation of Javanese culinary gastronomic cultural identity is represented in the self-expression of Javanese people through unen-unen and wewaler. The conclusion is that the representation of Javanese culinary cultural and gastronomic identity in the five songs is built on the intelligence of Javanese people's thinking as expressed in unen-unen and wewaler. This representation of cultural identity is affiliated with the uniqueness and characteristics of each culinary delight, adding to the diversity of Javanese culinary treasures.